Brain drain or brain gain of allied health professionals in Limpopo - Vosloo, Elbie (My University, 2009)
The term “brain drain” became a reality in South Africa after doors opened for South Africans in overseas markets and the emphasis moved from hospital bed based care to total health for all South Africans. The lack of services in rural areas seems a problem with focus on migration of health professionals between rural and urban areas, and even overseas markets, leaving a possible imbalance. More allied health professionals from previously disadvantaged groups are trained but the need in specifically the rural areas continues to rise. Recruitment and retention strategies were implemented for scarce skilled health professionals in the Public Service but no proof is available whether it is successful or not for the allied health professional group. The vacancy rates for allied health professional posts are reportedly too high despite the fact that more candidates are recruited from rural areas to be trained as professionals, hoping they will return to work in rural areas. Allied health professionals seem to be constantly on the move despite the strategies already implemented, reasons for this are unknown. The purpose of this study is to explore and determine if there is an imbalance of allied health workers in rural and urban areas within Limpopo Province. Secondly, it was to determine what factors may influence and contribute to allied health professional‟s decision to consider migration and thirdly to establish if the current recruitment and retention strategies are having the desired outcome. A survey was conducted over a period of three months with respondents representing the dietetic, physiotherapy, radiography, occupational therapy and speech and language therapy professions. The sample population was randomly selected as well as cluster sampling from the different districts within the Limpopo Province. Data was collected from a total of 122 respondents. xv Because the type of data collected was mainly nominal data, graphical and tabular descriptive techniques like frequencies, relative frequencies, tables and graphs were used to provide information. Numerical descriptive techniques were also used to calculate sample statistics and the only statistical technique that involves nominal data, the Chi-Squared Test was also applied. The findings of the research survey enabled the researcher to make final conclusions as well as specific recommendations to the target groups that may benefit from this study in order to change the “brain drain” to a “brain gain” situation for allied health professionals within the Limpopo Province.
Thesis (M.B.A.)--University of Limpopo,2009.
Keywords: Brain drain; South Africa; Health professionals; Rural and urban areas; 610.7376825; Brain drain - South Africa.